Activities of the Australian Medicago Genetic Resources Centre - Hughes S.J.; McLachlan D.R. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
The Australian Medicago Genetic Resources Centre (AMGRC) maintains the world's largest collection of Medicago species. In addition, over 10,000 lines of other temperate legume pasture species are also conserved. The centre conducts its genetic resources activities in accordance with internationally recognised standards. The seed increase program and protocols for characterisation and evaluation of germplasm are determined in close consultation with the immediate users of targeted lines. Currently there are changes occurring in the use and nature of the collection as a much wider range of pasture legume species are being conserved and evaluated than the traditional Medicago species. The centre is also increasing initiatives to actively promote and diversify the utilisation of the collection with future plans to provide germplasm for viticulture and ornamental horticulture research programs.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)